Short-Term Test-Retest Reliability of Electrically Evoked Cortical Auditory Potentials in Adult Cochlear Implant Recipients - Pike, Meghan; Biagio-de Jager, Leigh; le Roux, Talita; Hofmeyr, Louis M. (Frontiers in Neurology, 2020)
Background: Late latency auditory evoked potentials (LLAEPs) provide objective evidence of an individual’s central auditory processing abilities. Electrically evoked cortical auditory evoked potentials (eCAEPs) are a type of LLAEP that provides an objective measure of aided speech perception and auditory processing abilities in cochlear implant (CI) recipients. Aim: To determine the short-term test-retest reliability of eCAEPs in adult CI recipients. Design: An explorative, within-subject repeated measures research design was employed. Study sample: The study sample included twelve postlingually deafened, unilaterally implanted adult CI recipients with at least nine months of CI experience. Method: eCAEPs representing basal, medial and apical cochlear regions were recorded in the implanted ears of each participant. Measurements were repeated seven days after the initial assessment. Results: No significant differences between either median latencies or amplitudes at test and retest sessions (p>0.05) were found when results for apical, medial and basal electrodes were averaged together. Lower coefficient of variation values were found for measures of latency compared to amplitude for eCAEP measurements. Mean intraclass correlation coefficient (ICC) scores averaged across basal, medial and apical cochlear stimulus regions indicated that both consistency and agreement were statistically significant and ranged from moderate to excellent (ICC = 0.66–0.94, p<0.05). ICC confidence intervals did demonstrate considerable individual variability in both latency and amplitudes. Conclusion: eCAEP latencies and amplitudes demonstrated moderate to excellent short-term test-retest reliability. However, confidence intervals indicated individual variability in measurement consistency which is likely linked to attention and listening effort required from the CI recipients.